Problem:
Solve the equation for all values of x by completing the square.
x^2 + 4x + 3 = 0
remember the following:
To solve
![ax^2\text{ + bx +c= }0](https://img.qammunity.org/2023/formulas/mathematics/college/i0cnk7b86o0vaz79ymoi21srf3imw274g1.png)
by completing the square, we carry out the following steps:
1. Transform the equation so that the constant term, c, is only on the right-hand side. In our case:
![x^2\text{ + 4x = -3}](https://img.qammunity.org/2023/formulas/mathematics/college/eliwn65zkbsl1eul04l1lc8mkeirr1194i.png)
2. If a , the leading coefficient (the coefficient of the term x^2), is not equal to 1, divide both sides by a. Notice that in our case a = 1. Then, we don't do this step.
3. Add (b/2a)^2 to the right and the left side of the equation, that is:
![x^2\text{ + 4x + (}(b)/(2a))^2\text{= -3 + (}(b)/(2a))^2](https://img.qammunity.org/2023/formulas/mathematics/college/odu5jnxrtxv7m20xyon9vtqzpgin46257v.png)
in our case note that b = 4 and a = 1, so we have:
![x^2\text{ + 4x + (}(4)/(2))^2\text{= -3 + (}(4)/(2))^2](https://img.qammunity.org/2023/formulas/mathematics/college/mintbd0bxyqd4vqvc93qlbnszmcuxxk9l6.png)
this is equivalent to say:
![x^2\text{ + 4x + (2})^2\text{= -3 + (2})^2\text{ = -3+4}](https://img.qammunity.org/2023/formulas/mathematics/college/wxid27m7gtag2wypopgjih6k68m2yv8b8t.png)
this is equivalent to say
![x^2\text{ + 4x + (2})^2=1](https://img.qammunity.org/2023/formulas/mathematics/college/rc33v5vfiygsoewf63hcc1nz5azstpil4y.png)
this is equivalent to say:
![(x+2)^2=1](https://img.qammunity.org/2023/formulas/mathematics/college/aix5r5la62jh5z0fq80huojarjqk6o36n7.png)
now, we take the square root of both sides of the equation
![\sqrt[]{(x+2)^2}=\sqrt[]{1}](https://img.qammunity.org/2023/formulas/mathematics/college/icplh5qrkn4pydi12gdp79zb3ipvy26to3.png)
this is equivalent to say:
![x+2^{}=\pm1](https://img.qammunity.org/2023/formulas/mathematics/college/ze0ueoj2qa2x1u8brag5suwm29nxr9ucsw.png)
solve for x
![x=\pm1\text{ - 2}](https://img.qammunity.org/2023/formulas/mathematics/college/6gt297bqz8irmh7fwlwf6g90ndicvcwams.png)
then, we have two solutions:
![x=1-2\text{ = -1}](https://img.qammunity.org/2023/formulas/mathematics/college/7q05afwm0xm9oz91hym2po73d415zm4085.png)
and
![x=-1-2\text{ = -}3](https://img.qammunity.org/2023/formulas/mathematics/college/5cfzjrjouwzoahaw3s3j1yejwmfq025abr.png)
the two roots(zeros) are x = -1 and x = -3